Pregledi asimptomatskih žensk v pomenopavzi - ali delamo več škode kot koristi? - Pretnar-Darovec, Alenka (Zdravniški vestnik, 2003)
Background. As a rule postmenopausal women have been managed by the gynaecologist once a year when they came for a gynaecologic examination. More recent guidelines recommend a gynaecologic examination to be performed every three years, and collaboration of the registered nurse with cervical smear taking. Management of women in peri- and postmenopause does not depend only onPap smear, limited to be taken once per three years. Most women responding to a short survey are in favour of a yearly gynaecologic examination. Conclusions. A gynaecological examination should not represent the cervical smear taking only, but should aim at providing holistic management of the postmenopausal woman. The ideal solution to the problem is foundation of special centres, or at least consulting rooms for women in menopause, or, where this is not possible, it is recommended the postmenopausal women visits the gynaecologist for either gynaecologic examination or for counselling more frequently than advised for smear taking.
Keywords: Cervix Neoplasms; Cost-Benefit Analysis; diagnostika; ginekologija; klimakterij; Maternični vrat, novotvorbe; Ocena uspešnosti in stroškov; Pomenopavza; Postmenopause; Prevention And Control; Vaginal Smears; Vaginalni razmazi; zdravniški pregledi